Contemporary Oral Oncology : Biology, Epidemiology, Etiology, and Prevention - Kuriakose, Moni Abraham (Springer International Publishing : Imprint: Springer, 2017)
This is the first of four volumes that together offer an authoritative, in-depth reference guide covering all aspects of the management of oral cancer from a multidisciplinary perspective and on the basis of a strong scientific foundation. This volume, on tumor biology, epidemiology, etiology, emerging role of cancer stem cells and prevention of oral cancer, opens by discussing oral carcinogenesis in general and the role of particular carcinogens and human papillomavirus. Global epidemiology and changes in disease prevalence are then addressed. Up-to-date information is provided on emerging cancer biomarkers, and the biologic basis of personalized therapy is explained. Histopathological features of malignant and premalignant neoplasms and their relevance to management are described. Further chapters focus on the current status of chemoprevention, the management of oral submucous fibrosis, and the value of various diagnostic adjuncts. The volume concludes by critically evaluating the efficacy of oral screening methods.- Resumé vydavatel